(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A quality in education of lower central network with coaching and mentoring pass online system consisting of teachers, administrators by using the concept and activities of the mentoring system. The purposes were as 1) To Assess the promotion of knowledge and understanding of concepts used in the development of production and teacher development systems in relevant target groups consisting of teachers, administrators using concepts and activities, mentoring systems, Coaching and Mentoring and 2) To develop the system and the process of teaching and learning management by having teachers remove the knowledge management (KM) in classroom by developing a mentor for the target group with participating in the phase 1 project will apply the knowledge in real situations in the lower central region network schools and building a professional community of learning (Professional Learning Community: PLC) by the university professors do research to develop teaching and learning and develop teachers in small schools as well as "coaches" for teachers to use innovations developed for their students in this research using quantitative research methods and integrated experiments (Quantitative-Experiment Research) The researcher has set the framework for the research guidelines. The population for this research with selected purposive sampling by considering the context of responsibilities with university. In the network area of the lower central region which are small and voluntary schools of 30 schools, 98 teachers (science and math teachers), 22 university professors (teachers responsible for monitoring all 30 schools) for the academic year 2019. Data analysis using the statistics of percentage (%) average ( x ̅ ) standard Deviation (S.D.) and qualitative data analysis. The results of the research were findings: 1) Assessment in the promotion of knowledge and understanding of concepts used in the development of production and teacher development systems Develop relevant target groups consisting of teachers, administrators using concepts and activities, mentoring systems, coaching and mentoring the satisfaction at the highest level (x ̅ =4.74, S.D.=0.37) and 2) Development a system and learning process by having the teacher to remove the knowledge management (KM) in classroom consisting of 1) Learning Management with coaching and mentoring process, 2) Development of competency based learning with imagination (Competency Based on Imagination), 3) Supporting the process of building empirical knowledge (Construction of Knowledge), and 4) Performance Review for Creation of Innovation..